Shanghai Cooperation Organisation: Analysing Opportunities and Challenges for India - Ahmed, Jesmine (International Journal of Psychosocial Rehabilitation, 2020)
For making collective efforts to maintain peace, security and stability in Central Asia, SCO was formed. It is a permanent intergovernmental organisation to address global challenges and highlighted the need to tackle terrorism, separatism and extremism. In 2017, by joining SCO, India paved the way for a potential platform to advance India’s Connect Central Asia Policy. Moreover, the Central Asian states are also keen for India to play a bigger role in the region. But in order to succeed, India would have to improve its own standing in the region. However, this paper tries to analyse the evolution of Shanghai Cooperation Organisation in general and also examines how India’s strategic aims in Central Asia are reflected through its membership with SCO along with various opportunities and challenges faced by it in particular.